2007
DOI: 10.1007/s11845-007-0006-1
|View full text |Cite
|
Sign up to set email alerts
|

Limited options: a report on GP access to services

Abstract: Access to existing services must be increased, and significant resources must be put into the development of dedicated primary care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Though low, the response rate in the current study is comparable to similar Irish surveys in general practice reported in the literature [22]. In addition, the profile of characteristics for GPs responding to this survey (in terms of gender, age and rural/urban setting of practice) is similar to that reported for GPs nationally in a 2005 survey [23,24]. A t-test comparison revealed no significant differences for gender and total barrier scores; this may well be as a result of a type two error, due to small size.…”
Section: Discussionsupporting
confidence: 83%
“…Though low, the response rate in the current study is comparable to similar Irish surveys in general practice reported in the literature [22]. In addition, the profile of characteristics for GPs responding to this survey (in terms of gender, age and rural/urban setting of practice) is similar to that reported for GPs nationally in a 2005 survey [23,24]. A t-test comparison revealed no significant differences for gender and total barrier scores; this may well be as a result of a type two error, due to small size.…”
Section: Discussionsupporting
confidence: 83%
“…This finding may be highlighting a 'compensation' effect, whereby the smaller and more remote HSE West practices with less access to secondary health-care services invest in a greater portfolio of services for their patients. Previous studies also report a higher availability of medical equipment in rural practices regardless of the type of health-care system [6,[35][36][37].…”
Section: Discussionmentioning
confidence: 89%
“…We speculate that the high proportion of shoulder and upper limb presentations to the rheumatology service might reflect the level of access to musculoskeletal services in primary care, which is varied across different geographical regions within the Irish health care system. One study of Irish GP access to physiotherapy services reported that only 58% of GPs in urban areas had access to physiotherapy services . Earlier referral to physiotherapy by the GP within primary care might have avoided referral to the rheumatology service within secondary care.…”
Section: Discussionmentioning
confidence: 99%